Those who counter match-fixing fraudsters: voices from a multistakeholder ecosystem - Caneppele, Stefano (Crime, law and social change, 2020)
This study sheds light on the match-fixing ecosystem, with particular focus on those entities engaged in protecting the integrity of competitions. It analyzes the characteristics of match-fixers, as perceived by some anti-match-fixing stakeholders; the known processes of match-fixing and their evolution; and the interactions among stakeholders in the match-fixing ecosystem. Results show that while anti-match-fixing actors seem to have only a fuzzy idea of match-fixers’ characteristics, they appear to know quite well how fraudsters manipulate games. Meanwhile, fixers seem to have adapted their processes across time in response to harsher countermeasures according to two main strategies: layering, in which mules are used to place bets on multiple operators to conceal suspicious betting pattern algorithms, and diversification/displacement, in which fixers decide to pursue new betting options or to target minor leagues or other, less monitored sports. Some fixers did not have to adapt since in many countries police investigations remain rare and criminal sanction mild. Further research should encourage comparative perspectives beyond the European dimension, develop a more systematic effort to establish a sport fraudsters typology, and focus on non-betting-related sports manipulations.